THE USE OF BUSUU APPLICATION TO TEACH PHRASAL VERB - Fadhila, Syarifah Laila; Salam, Urai; Wardah, Wardah (Universitas Tanjungpura, 2025)
This study evaluates the effectiveness of using the Busuu application to teach phrasal verbs to Class X MIA 3 students at SMAN 1 Sungai Raya. Employing a pre-experimental design, the research focused on 35 students from a population of 420. Data collection included pretests and post-tests, following a sequence of pre-test, treatment using the Busuu app, and post-test. Statistical analysis revealed that students